A Review on Various Techniques of AI Defender - Gautam, Kamlesh (Journal of Advanced Research in Applied Artificial Intelligence and Neural Network, 2021)
Recent years, computer works on Artificial intelligence. In simple word, Artificial intelligence is an entirely automated technology, which works all work is done from automatically like a self-driving car, provide automatic protection from attackers for the system. AI protect from a known or unknown attack in the form of spam, spy, phishing and communication filtration. This all know, or unknown attack use collects data of the user, which is very harmful. AI understandably use to reduce applications of black-box, an adversarial attack. Artificial intelligence can use in robotics which is used in military power. The robot is more efficient than human, and it is very secure to find land mine and to use the proper attack on the enemy camp. Furthermore, it can reduce terrorism in any country. In the present time, the cybercrime is dangerous for every user under the network. Digitalization security, geographical security, browser security, and protection from all type of problem. How to cite this article: Gautam K, Sharma PK, Samriya M et al. A Review on Various Methods of AI Defender. J Adv Res Appl Arti Intel Neural Netw 2020; 4(1): 1-6.